Surprise hanging by the cord - Rao, Smitha S.; Kalburgi, E. B. (International Surgery Journal, 2017)
Testicular cancer is curable. Excellent cure rates have been met by standardized treatment. We present a 65-year-old male with irreducible swelling in the right groin. On examination, there was a right inguinoscrotal irreducible tender swelling. USG was suggestive of testicular tumour. Intraoperatively, there was a hard swelling in the groin arising from the cord with enlarged, hard testis. It was excised with a right high orchidectomy and was diagnosed as seminoma testis histopathologically. Histopathology confirmed seminoma testis and the patient was advised chemoradiation. Testicular tumours are a rare presentation at this age. Metastases to the inguinal region are seen in only about 2% of patients with testicular cancer; few have inguinal lymph-node spread and the rest have metastases to the cord. Therefore, high ligation of the spermatic cord is important. Radiotherapy in seminomas of testes have proven excellent results. Testicular tumours with secondary hyrocele can mislead diagnosis. In such cases the metastases would be restricted to local regions than distant metastases. This case is being reported in view of its rarity with review of literature.